Keakuratan Koding Diagnosis Gastroenteritis Berdasarkan ICD-10 pada Pasien Rawat Inap di Rumah Sakit TK II 02.05.01 dr. AK Gani Palembang - Limisran Limisran; Rifda Naura Fadilah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Accurate diagnosis coding based on the International Classification of Diseases, Tenth Revision (ICD-10) is essential for ensuring the quality of medical records, morbidity reporting, and hospital health information management. This study aimed to analyze the accuracy of ICD-10 coding for gastroenteritis diagnoses among inpatients at TK II 02.05.01 dr. AK Gani Hospital, Palembang, and to identify the remaining coding inaccuracies. A quantitative descriptive study with a retrospective design was conducted using inpatient medical records of gastroenteritis cases from the first quarter of 2025. Data were collected through structured observation based on ICD-10 guidelines and supported by interviews with coding personnel. The findings indicate that most gastroenteritis diagnoses were coded accurately, while only a small proportion of records contained coding inaccuracies. These inaccuracies were primarily related to the assignment of the fourth ICD-10 character used to specify the diagnosis. The results suggest that ICD-10 implementation in the hospital has generally been effective; however, greater attention to coding precision and clinical documentation is still required to further improve the quality of medical record data.